2011
DOI: 10.1007/s00170-011-3685-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient optimisation of machining processes based on technical specifications for surface roughness: application to magnesium pieces in the aerospace industry

Abstract: Magnesium is one of the lightest metallic materials and is well known and widely used in the aeronautic and aerospace industries. The pieces machined in these industrial fields must satisfy stringent surface roughness requirements to achieve a product quality that conforms to the design specifications. The aim of this investigation is to optimise efficiently the dry turning of magnesium pieces to achieve a surface roughness within technical requirements. A cost-effective and flexible statistical optimisation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…The surface roughness values obtained were within the range 0.19-0.82 µm for all the tests performed. From another side, Villeta et al [72] evaluated the turning of the UNS M11311 magnesium alloy. The influence of the machining parameters and different tool coatings was studied, finding again that the feed rate is the most important factor to explain the surface roughness (Ra).…”
Section: Turningmentioning
confidence: 99%
“…The surface roughness values obtained were within the range 0.19-0.82 µm for all the tests performed. From another side, Villeta et al [72] evaluated the turning of the UNS M11311 magnesium alloy. The influence of the machining parameters and different tool coatings was studied, finding again that the feed rate is the most important factor to explain the surface roughness (Ra).…”
Section: Turningmentioning
confidence: 99%
“…On the other hand, this approach would allow, if necessary, for an increase in the degree of complexity of the geometry of the test pieces from solid knowledge about the joint behaviour of the individual materials depending on the results that were obtained. We have previous experience in the machining of both materials, both in continuous turning (horizontal and facing) [47][48][49][50][51][52][53][54][55][56][57][58][59][60] and in intermittent turning [56][57][58][59][60]. The geometry of the specimens raised in the present study is a natural evolution of the geometries and materials previously studied separately that have just been mentioned.…”
Section: Methodsmentioning
confidence: 96%
“…Statistical analysis of the data. The statistical methodology carried out in order to analyze the results of the experimental design is briefly described in [54]. The variability of the surface roughness is modelled through the analysis of variance (ANOVA) over the average roughness values, Ra, identifying the most influential factors and interactions on the surface finish.…”
Section: Methodsmentioning
confidence: 99%
“…From another side, Sayit et al [18] also identified a negative effect of the feed rate in discontinuous turning on the surface roughness, evaluating feed rates from 0.11 to 0.32 mm/rev. When using feed rates up to 0.1 mm/rev, the surface roughness values are below a range suited for aerospace and aeronautic fields (0.8<Ra<1.6 μm) [36]. However, when machining with the highest feed rate (0.2 mm/rev), the surface roughness is clearly above the aforementioned range.…”
Section: Surface Roughnessmentioning
confidence: 91%
“…For the feed rate selection, work by Villeta et al [36] is taken into account, though slightly higher values of the feed rate are selected. Thus, feed rates from 0.05 to 0.2 mm/rev are selected.…”
Section: Methodsmentioning
confidence: 99%